Assessment of Young Swimmers` Technique with Tec Pa Tool - Papadimitriou, K.; Papadimitriou, N.; Gourgoulis, V.; Barkoukis, V.; Loupos, D. (Central European Journal of Sport Sciences and Medicine, 2021)
Aim of the current study was to examine the reliability and validity of a new tool, developed for the assessment of young swimmers` technique in all swimming strokes. The sample of the study was 119 swimmers (63 boys and 56 girls), aged 8 to 12 years old. To evaluate swimmers` technique, each of them performed 15m for each one of the swimming strokes in individual medley order. A digital camera, placed 5m above the pool`s surface, recorded the swimming bouts. Three experienced swimming coaches evaluated the recorded videos with the new technique`s evaluation tool named Tec Pa. Tec Pa assess six important key points of swimming technique in each stroke. According to the results no statistical significant differences were showed between the scores of the swimmers` evaluation by the three coaches (p > 0.05). Moreover, the association between the scores was statistically significant high (t = 0.863; p < 0.05). The findings of the current study reveal that Tec Pa is valid and reliable for the young swimmers` technique evaluation, with high strength of association. Also, Tec Pa can be used by the coaches to enhance the free observation method, which is mainly used, in young swimmers.